2018
DOI: 10.1002/adbi.201800240
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Stiffness Modulation of Cell‐Laden Protein–Polymer Hydrogels in Response to User‐Specified Stimuli Including Light

Abstract: Although mechanical signals presented by the extracellular matrix are known to regulate many essential cell functions, the specific effects of these interactions, particularly in response to dynamic and heterogeneous cues, remain largely unknown. Here, a modular semisynthetic approach is introduced to create protein–polymer hydrogel biomaterials that undergo reversible stiffening in response to user‐specified inputs. Employing a novel dual‐chemoenzymatic modification strategy, fusion protein‐based gel crosslin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 77 publications
(84 reference statements)
0
99
0
Order By: Relevance
“…In preliminary work discussed previously, repeated stiffening and softening of hydrogel materials containing encapsulated 3T3 fibroblasts yielded differential activation as compared with statically stiff or soft materials. [ 55 ] Extension of this work in vivo would further elucidate the role of dynamic network stiffness on cell fate. [ 15,75 ]…”
Section: Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…In preliminary work discussed previously, repeated stiffening and softening of hydrogel materials containing encapsulated 3T3 fibroblasts yielded differential activation as compared with statically stiff or soft materials. [ 55 ] Extension of this work in vivo would further elucidate the role of dynamic network stiffness on cell fate. [ 15,75 ]…”
Section: Perspectivesmentioning
confidence: 99%
“…Liu et al recently demonstrated reversible photoreversible stiffening of hydrogel biomaterials crosslinked with a diazide‐modified LOV2‐Jα fusion using SPAAC. [ 55 ] The conformation change of the LOV2‐Jα interaction is traceable by UV–vis spectroscopy, with 470 nm irradiation nearly bleaching the visible absorbance, which can be recovered over time in the dark (Figure 5C). Once formed, the hydrogel can be repeatedly softened and stiffened again over time with very brief 470 nm irradiation windows (Figure 5D); this process that can be cycled hundreds of times with no measurable hysteresis.…”
Section: Wavelength‐dependent Strategies For Introducing Dynamic Matementioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al have looked beyond stimuli‐driven behavior that results in a permanent shape change or degradation of a cell‐laden hydrogel by developing materials that are capable of cyclic control of polymer stiffness over time . The researchers developed protein‐polymer hybrid hydrogels that could undergo reversible stiffening in response to environmental cues by engineering protein cross‐linkers that exhibit different conformations and end‐to‐end lengths in response to an external stimulus.…”
Section: Responsive Biointegrated Hydrogelsmentioning
confidence: 99%
“…[7] Recent research has enhanced our ability to imbue scaffolds with temporal information that is transiently activated by stimuli such as light, enzymes, pH, complementary ligands, or an integrated combination of multiple stimuli. [2,3,815]…”
mentioning
confidence: 99%